From Ten Steps to Ten themes: Consequential Contributions in the Collective Compositions of Ray C. Rist - Michael Patton (Journal of MultiDisciplinary Evaluation)
Background: This article is part of a collection recognizing, appreciating, and celebrating the substantial lifetime evaluation contributions of Ray C. Rist.